Nematocidal effect of Piper retrofractum Vahl on morphology and ultrastructure of Strongyloides stercoralis third-stage infective larvae - D. Riyong (2020)
Copyright © The Author(s) 2020. Published by Cambridge University Press. In a previous research work aimed at discovering natural helminthicides as alternatives to conventional synthetic drugs, Piper retrofractum fruit hexane extract (PHE) has been shown to possess promising nematocidal activity against the third-stage infective larvae of Strongyloides stercoralis. Thus, this study was designed to evaluate the chemical composition and the impact of PHE on symptom and structural alterations of S. stercoralis. Chemical analysis of PHE by gas chromatography-mass spectrometry demonstrated 26 different compounds, constituting 100% of the total composition. The main components were 4-acetylphenyl (4-benzoylphenoxy) acetate (14.86%) and octyl methoxycinnamate (12.72%). Nematocidal bioassays revealed promising potential of PHE against S. stercoralis larvae, with an LC50 value of 0.059 mg/ml, while the reference drug ivermectin exerted higher efficacy, with an LC50 value of 0.020 μg/ml. Behavioural observations under light microscopy revealed that PHE-treated S. stercoralis larvae moved slowly, became paralysed and eventually died during 24 h of incubation. The dead larvae appeared under light microscope as straight worms with unknown vacuoles of different sizes inside their internal bodies. Morphological alterations of the PHE-treated S. stercoralis larvae, such as straight bodies with swollen cuticle, faded transverse annulations and faded longitudinal striations, as well as shallow and smooth lateral longitudinal grooves, were seen clearly under scanning electron microscopy. Ultrastructural changes in the treated larvae, such as protruded lateral longitudinal grooves, loose muscle with vacuolation, dissociation between the hypodermis and cuticle and marked intracellular disorganization with vacuolation, were detected under transmission electron microscopy. The results of this study provide evidence that PHE is toxic against S. stercoralis and also a potential new alternative for anti-Strongyloides chemotherapy.